The various pathological manifestations of a lightning strike exemplified in a single four-fatality incident – A case report and review of a literature. (September 2022) - Pasieka, Paweł; Polak, Dagna; Pasieka, Patrycja; Lechowicz, Daria; Kisiołek, Laura; Warmuz, Konrad; Konopka, Tomasz; Moskała, Artur; Rzepecka-Woźniak, Ewa; Juźwik, Ewa; Strona, Marcin; Kołodziej, Jan; et al.
Highlights: Despite some decline of fatalities in recent years, lightning strikes are one of leading causes of weather-induced death. There are numerous varying manifestation of lightning strikes, sometimes making the identification of cause of death problematic. Although the vast majority of lightning strike cases is non-fatal, lightning is capable of causing serious damage to virtually all organs and injure multiple victims with one strike. It is crucial to consider lightning strike when examining open-air death of unclear origin. Abstract: The lightning strike is one of leading cases of weather-related death worldwide. We present an unusual case of four fatality-lightning strike with various pathological manifestations. All victims died from a single lightning strike in the mountains that also caused injury to 156 other people. All victims had mechanical damage and rock damage that are typical for lightning strikes in the mountainside. Another lesions indicative of lightning strike and electrical damage were, among others: burnt and torn clothes (all cases) current marks (Cases 1, 2 and 3) and Lichtenberg figures along with flashover marks on Case 1. In the review we described the pathophysiological mechanisms of lightning-induced lesions and injuries and epidemiological trends of lightning-strike deaths. Our study exemplifies various manifestations of lightning strikes on forensic examination and underlines the necessity to take lightning strike into consideration when investigating open-air deaths of unclear origin.